Teachers as leaders - Ravit, Amir; Keren, Grinberg (IJRDO - Journal of Applied Management Science, 2016)
Fact that it is a moral issue. Teachers have potential ability to affect mainly the different systems within the school and beyond. Teacher leadership is reflected in actions which steppes not only the class, or the school environment, but to the community as a whole. The teacher, as an agent of socialization, are actively involved in the creation and institutionalization of new systems of behaviors and values chain designed to improve the quality of life of the community in the long run. The teacher is the person who may bring systemic change and for improving the quality of information and what they are comfortable .functioning in school (Bugler, 2000) assumptions related to the functioning of principals and teachers in the school. They must recognize that the manager is not the only source of leadership in the teaching educational institution, but each member of staff can assume leadership responsibilities and should do between its units, leaves teachers considerable leeway to influence school performance. If .so the school principal creates an atmosphere of cooperation and encourage the staff to take the .initiative and act, created fertile ground for teacher leadership can come from it